MARKET ORIENTATION, ENTREPRENEURIAL ORIENTATION DAN BUSINESS PERFORMANCE PADA USAHA MIKRO KECIL DI DESA WISATA DAERAH ISTIMEWA YOGYAKARTA - Adhi Prakosa; Ahsan Sumantika (Jurnal Manajemen, 2018)
This study aims to test relationships between market orientation, entrepreneurial orientation, and business performance in small firm that located in tourist village in Yogyakarta. Independent variable is the market orientation, and entrepreneurial orientation. The dependent variable is business performance. The data collection is done directly by using a survey questionnaire. Hypothesis testing is done using multiple linear regression. Results can be concluded that the market orientation, and entrepreneurial orientation affects the business performance